Iron-reducing bacteria decompose lignin by electron transfer from soil organic matter - Merino C.; Kuzyakov Y.; Godoy K.; Jofré I.; Nájera F.; Matus F. (2021)
Iron-reducing bacteria (IRB) are crucial for electron transfer in anaerobic soil microsites. The utilization of the energy gathered by this mechanism by decomposers of organic matter is a challenging and fascinating issue. We hypothesized that bacteria reducing Fe(III) (oxyhydr)oxides to soluble Fe(II) obtain electrons from reduced soil organic matter (SOMr) involving lignin oxidation. Iron-reducing bacteria were isolated from topsoils of various climates (humid temperate, cold temperate, subpolar), vegetation types (mostly grasslands and forests), and derived from various parent materials treatments assigned as Granitic, Volcanic-allophanic, Fluvio-glacial, Basaltic-Antarctic and Metamorphic. After the screening of IRB by phospholipid fatty acid (PLFA) analysis and PCR identification (full-length 16S rDNA), the IRB were inoculated to 20 samples (five soils and 4 replicates) and a broad range of parallel processes were traced. Geobacter metallireducens and Geobacter lovleyi were the main Geobacteraceae-strains present in all soils and strongly increased the activity of ligninolytic enzymes: lignin peroxidase and manganese peroxidase. Carbon dioxide (CO2) released from IRB-inoculated soils was 140% higher than that produced by Fenton reactions (induced by H2O2 and Fe(II) addition) but 40% lower than in non-sterile soils. CO2 release was closely correlated with the produced Fe (II) and H2O2 consumption. The highest CO2 was released from Basaltic-Antarctic soils with the highest Fe content and was closely correlated with lignin depolymerization (detection by fluorescence images). All IRB oxidized the lignin contained in the SOM within a wide pH range and in soils from all parent materials. We present a conceptual model showing electron shuttling from SOM containing lignin (as a C and energy source) to IRB to produce energy and promote Fe(III) (oxyhydr)oxides reduction was proposed and discussed.